Solid electrolyte, electrolyte layer and battery

By developing solid electrolytes of hexagonal perovskite-related compounds, the limitation of SOFC working at high temperatures is solved, the effect of high conductivity at low temperatures is achieved, and the application range and practicality of fuel cells are improved.

CN113316557BActive Publication Date: 2025-02-25TOKYO INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080010123.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-24
Filing Date
2020-01-24
Publication Date
2025-02-25
Estimated Expiration
2040-01-24

AI Technical Summary

Technical Problem

Existing solid oxide fuel cells (SOFCs) need to operate at high temperatures to ensure oxide ion conductivity, resulting in increased equipment complexity and energy consumption, limiting their application range.

Method used

A solid electrolyte containing hexagonal perovskite-related compounds was developed, with the general formula of Ba7-αNb(4-x-y)Mo(1+x)MyO(20+z), by adjusting the element ratio and crystal lattice in the compound. Constant, achieves the effect of high conductivity at low temperatures.

Benefits of technology

It realizes the high conductivity under low temperature conditions (300~1200℃), reduces the dependence on high-temperature equipment, and improves the practicality and application range of SOFC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113316557B_ABST
    Figure CN113316557B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte having high electrical conductivity even in a low temperature range. A solid electrolyte, an electrolyte layer using the solid electrolyte, and a battery, wherein the solid electrolyte is a solid electrolyte containing a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (1). 7‑α Nb (4‑x‑y) Mо (1+x) M y O (20+z) ···(1)[In formula (1), M is a cation of at least one element. α is a Ba deficiency, which represents a value greater than 0 and less than 0.5, x represents a value greater than -1.1 and less than 1.1, y represents a value satisfying greater than 0 and less than 1.1, and z represents a non-stoichiometric amount of oxygen, which represents a value greater than -2.0 and less than 2.0. In formula (1), |x|+y≥0.01 is satisfied.]
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte used in a solid electrolyte layer of a fuel cell or the like, and an electrolyte layer and a battery using the solid electrolyte. Background Art

[0002] Among the fuel cells being studied in recent years, solid oxide fuel cells (hereinafter referred to as "SOFCs") have particularly high power generation efficiency, do not require fuel reforming equipment, and have excellent long-term stability. Therefore, they have the potential to be widely used in household and commercial applications and are attracting attention.

[0003] SOFC is composed of a solid electrolyte-electrode stack formed by setting a fuel electrode and an air electrode on both sides of a solid electrolyte layer. 2- ) As a conductive ceramic, yttria-stabilized zirconia (ZrO2-Y2O3) (hereinafter referred to as "YSZ") is known.

[0004] As the solid electrolyte used in SOFC, other compounds with high electrical conductivity, such as conductive oxide ions (O 2- ), proton (H + ) and other ions showing high ionic conductivity. Patent document 1 discloses a crystalline inorganic compound capable of conducting at least one carrier selected from the group consisting of anions, cations, protons, electrons and holes. Non-patent document 1 discloses Ba7Nb4MoO as a hexagonal perovskite-related compound with high ionic conductivity (σ). 20 .

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6448020

[0008] Non-patent literature

[0009] Non-patent document 1: Sacha Fop, Novel oxide ion conductors in the hexagonal perovskite family, uk.Bl.Ethos.701786, [accessed on December 25, 2011], Internet <URL:https: / / ethos.bl.uk / OrderDetails.do?uin=uk.bl.ethos.701786> Summary of the invention

[0010] Problems to be solved by the invention

[0011] In order to obtain sufficient performance, SOFCs using YSZ as solid electrolytes need to be operated at high temperatures. The reason is that YSZ needs a high temperature of about 700°C or higher to ensure the oxide ion conductivity required by the battery. In order to operate the battery at such a high temperature of 700°C or higher, other devices such as blocking or cooling are required in such a way that the operating environment, space, and battery are kept at high temperatures and other environments do not become high temperatures.

[0012] It is predicted that if SOFC can be operated at low temperatures, the above-mentioned limitations on operating it at high temperatures can be alleviated, and the practicality of SOFC can be significantly improved. In addition, it is predicted that even in the utilization methods other than SOFC of solid electrolytes, the scope of application will be greatly expanded due to the ability to operate at low temperatures. Therefore, solid electrolytes with high electrical conductivity at low temperatures are strongly desired.

[0013] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a solid electrolyte having high electrical conductivity even in a low temperature range, and an electrolyte layer and a battery using the solid electrolyte.

[0014] Methods for solving problems

[0015] In order to solve the above-mentioned problems, the present invention has the following aspects.

[0016] [1] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (1).

[0017] Ba 7-α Nb (4-x-y) Mо (1+x) M y O (20+z) ···(1)

[0018] [In the formula (1), M is a cation of at least one element selected from the group consisting of Ag, Al, At, Au, Be, Bi, Br, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Hf, Hg, Ho, I, In, Ir, La, Li, Lu, Mg, Mn, Na, Nb, Nd, Ni, Np, Os, P, Pb, Pd, Po, Pr, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sm, Sn, Sr, Ta, Tb, Tc, Te, Ti, Tl, Tm, U, V, W, Xe, Y, Yb, Zn and Zr. α is the Ba deficiency, which is a value greater than 0 and less than 0.5, x is a value greater than -1.1 and less than 1.1, y is a value greater than 0 and less than 1.1, and z is the non-stoichiometric amount of oxygen, which is a value greater than -2.0 and less than 2.0. In formula (1), |x|+y≥0.01 is satisfied.]

[0019] [2] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (2).

[0020] Ba 7-α Nb (4-x―y) Mо (1+x) M y O (20+z) ···(2)

[0021] [In formula (2), M is a cation of at least one element selected from the group consisting of W, V, Cr, Mn, Ge, Si and Zr. α is the Ba deficiency, which represents a value greater than 0 and less than 0.5, x represents a value greater than -1.1 and less than 1.1, y represents a value greater than 0 and less than 1.1 and satisfies |x|+y≥0.01, and z represents the non-stoichiometric amount of oxygen, which represents a value greater than -2.0 and less than 2.0.]

[0022] [3] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by any one of the following general formulas (3) to (13).

[0023] 7B (4-x) Mо (1+x) O (20+z) ···(3)

[0024] [In formula (3), x represents a value of -1.1 to -0.01 or 0.01 to 1.1, and z represents the non-stoichiometric value of oxygen and represents a value of -2.0 to 2.0.]

[0025] 7B(4-y) MоM y O (20+z) ···(4)

[0026] [In formula (4), M is a cation of at least one element selected from the group consisting of V, Mn, Ge, Si and Zr. y represents a value of 0.01 to 1.1, and z represents the non-stoichiometric value of oxygen, which represents a value of -2.0 to 2.0.]

[0027] Ba7Nb4M (1-y) M y O (20+z) ···(5)

[0028] [In formula (5), M is a cation of at least one element selected from the group consisting of V and Mn. z is the non-stoichiometric value of oxygen and represents a value of not less than -2.0 and not more than 2.0, and y represents a value of not less than 0.01 and not more than 1.1.]

[0029] 7B (4-y) MоCr y O (20+z) ···(6)

[0030] [In formula (6), z represents the non-stoichiometric amount of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.1.]

[0031] 7B (4-y) MoW y O (20+z) ···(7)

[0032] [In formula (7), z represents the non-stoichiometric amount of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.1.]

[0033] oeLh (1-x) V (1+x) O (8.5+z) ···(8)

[0034] [In formula (8), x represents a value of -0.8 to 0.2, and z represents a value of -1.0 to 1.0, which is the non-stoichiometric value of oxygen.]

[0035] 3MO (1-x) Ti (1+x) O (8+z) ···(9)

[0036] [In formula (9), x represents a value of -0.3 or more and 0.1 or less, and z represents a value of -0.1 or more and 0.3 or less in terms of non-stoichiometric oxygen.]

[0037] Ba7Ca2Mn5O (20+z) ···(10)

[0038] [In formula (10), z is the non-stoichiometric amount of oxygen and represents a value of -1.0 or more and 1.0 or less.]

[0039] Ba 2.6 Ca 2.4 La4Mn4O (19+z) ···(11)

[0040] [In formula (11), z is the non-stoichiometric amount of oxygen and represents a value of -1.0 or more and 1.0 or less.]

[0041] La2Ca2MnO (7+z) ···(12)

[0042] [In formula (12), z is the non-stoichiometric amount of oxygen and represents a value of -1.0 or more and 1.0 or less.]

[0043] Ba5M2Al2ZrO (13+z) ···(13)

[0044] [In formula (13), M represents any one of Gd, Dy, Ho, Er, Tm, Yb or Lu. z represents the non-stoichiometric amount of oxygen and represents a value greater than -1.0 and less than 1.0.]

[0045] [4] The solid electrolyte according to [1] or [2], wherein x is greater than or equal to 0.06 and less than or equal to 0.30.

[0046] [5] The solid electrolyte according to [3], wherein the compound is a compound represented by the general formula (3), and x is 0.06 to 0.30.

[0047] [6] The solid electrolyte according to [4] or [5], wherein x is greater than or equal to 0.19 and less than or equal to 0.21.

[0048] [7] The solid electrolyte according to [2], wherein the a-axis length, b-axis length, and c-axis length of the lattice constant of the compound are The angles α, β, and γ (o) for equation (2) are 5.35 <a<6.56、5.35<b<6.56、15.14<c<18.52、89<α<91、89<β<91、119<γ<121。

[0049] [8] The solid electrolyte according to [3], wherein the a-axis length, b-axis length, and c-axis length of the lattice constants of the compound are For equations (3) to (7), the angles α, β, and γ (o) are respectively in the numerical ranges of 5.35 < a < 6.56, 5.35 < b < 6.56, 15.14 < c < 18.52, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (8), they are respectively 5.23 < a < 6.4, 5.23 < b < 6.4, 18.96 < c < 23.19, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (9), they are respectively 5.34 < a < 6.54, 5.34 < b < 6.54, 19.12 < c < 23.39, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (10), they are respectively 5.23 < a < 6.41, 5.23 < b < 6.41, 46.23 < c < 56.51, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (11), they are respectively 8.85 < a < 10.83, 5.11 < b < 6.26, 14.07 < c < 17.21, 89 < α < 91, 100 < β < 104, 89 < γ < 91; for equation (12), they are respectively 5.05 < a < 6.19, 5.05 < b < 6.19, 15.57 < c < 19.03, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (13), they are respectively 5.35 < a < 6.55, 5.35 < b < 6.55, 22.23 < c < 27.18, 89 < α < 91, 89 < β < 91, 119 < γ < 121.

[0050] [9] The solid electrolyte according to any one of [1] to [8], which is a solid electrolyte used as an oxide ion (O 2- ) conductor and is used under temperature conditions of 300 to 1200 °C.

[0051]

[10] For the solid electrolyte according to any one of [1] to [9], when measuring the conductivity at 300 °C, the conductivity represented by log[σ (S cm -1 )] is -7 or more.

[0052]

[11] The solid electrolyte according to any one of [1] to

[10] , which is a solid oxide fuel cell (SOFC), sensor, battery, electrode, electrolyte, oxygen concentrator, oxygen separation membrane, oxygen permeation membrane, oxygen pump, catalyst, photocatalyst, electrical / electronic / communication equipment, equipment for energy / environment related use, or optical equipment.

[0053]

[12] The solid electrolyte according to any one of [1] to

[11] , which is used for an electrolyte layer used in a solid oxide fuel cell (SOFC), a sensor, an oxygen concentrator, an oxygen separation membrane, an oxygen permeable membrane or an oxygen pump.

[0054]

[13] An electrolyte layer comprising the solid electrolyte described in any one of [1] to

[12] .

[0055]

[14] A battery comprising the electrolyte layer containing the solid electrolyte according to

[13] .

[0056]

[15] The battery according to

[14] , which is a solid oxide fuel cell (SOFC).

[0057] In addition, this embodiment has other aspects as follows.

[0058] [1A] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (1).

[0059] Ba 7-α Nb (4-x-y) Mо (1+x) M y O (20+z) ···(1)

[0060] [In formula (1), M is a cation of at least one element selected from the group consisting of Ag, Al, At, Au, Be, Bi, Br, Cd, Co, Cr, Cu, Fe, Ga, Ge, Hf, Hg, I, In, Ir, Li, Mg, Mn, Mo, Nb, Ni, Np, Os, P, Pb, Pd, Po, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sn, Ta, Tb, Tc, Te, Ti, Tl, U, V, W, Xe, Zn and Zr. α is the Ba deficiency, which represents a value of 0 to 0.5, x represents a value of -0.15 to -0.01 or 0.01 to 0.35, y represents a value of 0.01 to 0.35, and z represents the non-stoichiometric amount of oxygen, which represents a value of -0.2 to 0.2.]

[0061] [2A] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (2).

[0062] Ba 7-α Nb (4-x―y) Mо (1+x) M y O (20+z) ···(2)

[0063] [In formula (2), M is a cation of at least one element selected from the group consisting of W, V, Cr, Ge, Si and Zr. α is the Ba deficiency, which represents a value of 0 to 0.5, x represents a value of -0.15 to -0.01 or 0.01 to 0.35, y represents a value of 0.01 to 0.35, and z represents the non-stoichiometric amount of oxygen, which represents a value of -0.2 to 0.2.]

[0064] [3A] A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by any one of the following general formulas (3) to (6).

[0065] 7B (4-x) Mо (1+x) O (20+z) ···(3)

[0066] [In formula (3), x represents a value of -0.15 to -0.01 or 0.01 to 0.20, and z represents the non-stoichiometric value of oxygen and represents a value of -0.2 to 0.2.]

[0067] 7B (4-y) MоM y O (20+z) ···(4)

[0068] [In formula (4), M is a cation of at least one element selected from the group consisting of W, V, Ge, Si and Zr. y represents a value of 0.01 to 0.2, and z represents the non-stoichiometric value of oxygen, which represents a value of -0.2 to 0.2.]

[0069] Ba7Nb4M (1-y) V y O (20+z) ···(5)

[0070] [In formula (5), z represents the non-stoichiometric amount of oxygen and is a value of -0.2 to 0.2, and y represents a value of 0.01 to 0.2.]

[0071] 7B (4-y) MоCr y O (20+z) ···(6)

[0072] [In formula (6), z represents the non-stoichiometric amount of oxygen and is a value of -0.2 to 0.2, and y represents a value of 0.01 to 0.35.]

[0073] [4A] The solid electrolyte according to any one of [1A] to [3A], wherein x is 0.06 or more and 0.12 or less.

[0074] [5A] The solid electrolyte according to [4A], wherein x is 0.09 or more and 0.11 or less.

[0075] [6A] The solid electrolyte according to any one of [1A] to [5A], in the above compound, the a-axis length, b-axis length, and c-axis length of the lattice constant, and the α angle, β angle, and γ angle (°) are respectively in the numerical ranges of 5.83 < a < 6.08, 5.83 < b < 6.08, 16.4 < c < 17.17, 89 < α < 91, 89 < β < 91, and 119 < γ < 121.

[0076] [7A] The solid electrolyte according to any one of [1A] to [6A], when measuring the conductivity at 300 °C, the conductivity represented by log[σ (S cm -1 )] is -6.2 or more.

[0077] Advantages of the Invention

[0078] According to the present invention, a solid electrolyte having high conductivity even in a low temperature region can be obtained, and an electrolyte layer and a battery using the solid electrolyte. Brief Description of the Drawings

[0079] Figure 1 is a chart showing the X-ray diffraction (XRD) pattern of Test Example 1 of the present embodiment.

[0080] Figure 2 is a chart showing the XRD pattern of Test Example 2 of the present embodiment.

[0081] Figure 3 is a chart showing the XRD pattern of Test Example 3 of the present embodiment.

[0082] Figure 4 is a chart showing the XRD pattern of Test Example 4 of the present embodiment.

[0083] Figure 5 is a chart showing the XRD pattern of Test Example 5 of the present embodiment.

[0084] Figure 6 is a chart showing the XRD pattern of Test Example 6 of the present embodiment.

[0085] Figure 7 is a chart showing the XRD pattern of Test Example 7 of the present embodiment.

[0086] Figure 8 ​​​​​​​​] is a chart showing the XRD pattern of Test Example 8 of this embodiment.

[0087] [ Fig. 9 ] is a chart showing the XRD pattern of Test Example 9 of this embodiment.

[0088] [ Fig.10 ] is a chart showing the XRD pattern of Test Example 10 of this embodiment.

[0089] [ Fig.11 ] is a chart showing the XRD pattern of Test Example 11 of this embodiment.

[0090] [ Fig.12 ] is a chart showing the XRD pattern of Test Example 12 of this embodiment.

[0091] [ Fig.13 ] is a chart showing the XRD pattern of Test Example 13 of this embodiment.

[0092] [ Fig.14 ] is a chart showing the XRD pattern of Test Example 14 of this embodiment.

[0093] [ Fig.15 ] is a chart showing the XRD pattern of Test Example 15 of this embodiment.

[0094] [ Fig.16 ] is a chart showing the XRD pattern of Test Example 16 of this embodiment.

[0095] [ Fig.17 ] is a chart showing the XRD pattern of Test Example 17 of this embodiment.

[0096] [ Fig.18 ] is a chart showing the XRD pattern of Test Example 18 of this embodiment.

[0097] [ Fig.19 ] is a chart showing the XRD pattern of Test Example 19 of this embodiment.

[0098] [ Fig. 20 ] is a chart showing the XRD pattern of Test Example 20 of this embodiment.

[0099] [ Fig.21 ] is a chart showing the XRD pattern of Test Example 21 of this embodiment.

[0100] [ Fig. 22 ] is a graph showing the comparison of the electrical conductivity of Test Example 1 and Test Example 6 of this embodiment and YSZ.

[0101] [ Fig.23] represents the Ba7Nb2O3 in which the Mo excess x of the test example of this embodiment is 0.02 to 0.10. (4-x) Mо (1+x) O (20+z) In this graph, for comparison, the conductivity of Ba7Nb4MoO2 in which the excess Mo content x is 0.0 in the test example of this embodiment is also shown. 20 conductivity.

[0102] [ Fig.24 ] represents the Ba7Nb with Mo excess x of 0.10 to 0.18 in the test example of this embodiment. (4-x) Mо (1+x) O (20+z) In this graph, for comparison, the conductivity of Ba7Nb4MoO2 in which the excess Mo content x is 0.0 in the test example of this embodiment is also shown. 20 conductivity.

[0103] [ Fig.25 ] represents the Ba7Nb2O3 in which the doping amount y of the cations of each element of Cr, W, V, Si, Ge, and Zr is 0.1 in the test example of this embodiment. (4-y) MоM y O (20+z) and Ba7Nb4M0 with a doping amount y of V cations of 0.1 (1-y) V y O (20+z) Graph of the electrical conductivity.

[0104] [ Fig.26 ] represents the Ba7Nb with the Cr doping amount y of 0.10 to 0.30 in the test example of this embodiment. (4-y) MоCr y O (20+z) Graph of the electrical conductivity.

[0105] [ Fig. 27 ] is a graph showing the oxygen partial pressure dependence of the electrical conductivity at 900°C in Test Example 1 of the present embodiment.

[0106] [ Fig.28 ] is a graph showing the relationship between the electromotive force and the oxygen partial pressure of the oxygen concentration difference cell at 800°C in Test Example 6 of the present embodiment.

[0107] [ Fig.29 ] is a graph showing the relationship between the electromotive force and the oxygen partial pressure of the oxygen concentration difference cell at 900°C in Test Example 6 of this embodiment.

[0108] [ Fig.30 ] represents Ba7Nb4MoO as Test Example 22 20 of the crystal structure.

[0109] [ Fig.31 ] represents Ba7Nb as Test Examples 22 to 27 (4-x) MO (1+x) O (20+z) Graph of the XRD pattern.

[0110] [ Fig.32 ] For Test Examples 28-37 having different compositions, Ba7Nb (4-x) MO (1+x) O (20+z) XRD determination diagram of .

[0111] [ Fig.33 ](a) Temperature dependence of Ba7Nb as Test Examples 22 to 27 (4-x) MO (1+x) O (20+z) (b) For Test Examples 28 to 35 having other compositions, the conductivity of Ba7Nb is shown in terms of temperature dependence. (4-x) MO (1+x) O (20+z) conductivity.

[0112] [ Fig.34 ] The composition dependence of Ba7Nb2 as test examples 22 to 35 at a certain temperature is shown. (4-x) MO (1+x) O (20+z) conductivity.

[0113] [ Fig.35 ] represents Ba7Nb as test examples 40 to 44 and 46 (4-y) MоCr y O (20+z) Graph of the XRD pattern.

[0114] [ Fig.36 ] The temperature dependence of Ba7Nb as test examples 40 to 44 and 46 is shown. (4-y) MоCr y O (20+z) conductivity.

[0115] [ Fig.37 ] The composition dependence of Ba7Nb as test examples 22, 40 to 44 and 46 is shown (4-y) MоCr y O (20+z) conductivity.

[0116] [ Fig.38 ] represents the Ba7Nb (4-y) MoW y O (20+z)Graph of the XRD pattern.

[0117] [ Fig.39 ]For Ba7Nb (4-y) MoW y O (20+z) The total conductivity of Test Examples 52 to 58, 81, and 82 in FIG. 8 is expressed in terms of temperature dependence.

[0118] [ Fig.40 ] For Ba7Nb as Test Examples 22, 52 to 58, 81, and 82 (4-y) MoW y O (20+z) The total conductivity is expressed in terms of composition dependence.

[0119] [ Fig.41 ] is a chart showing the XRD patterns of Test Examples 38, 39, 45, and 47 to 51.

[0120] [ Fig.42 ] The conductivity of Test Examples 38, 39, and 47 to 50 is shown in terms of temperature dependence.

[0121] [ Fig.43 ] represents Ba3WVO of Test Examples 59 to 67 8.5 The crystal structure of the material.

[0122] [ Fig.44 ] represents Ba3W of Test Examples 59 to 67 (1-x) V (1+x) O (8.5+z) Graph of the XRD pattern.

[0123] [ Fig.45 ] For Ba3W of Test Examples 59 to 67 (1-x) V (1+x) O (8.5+z) The conductivity is expressed in terms of temperature dependence.

[0124] [ Fig.46 ] For Ba3W of Test Examples 59 to 67 (1-x) V (1+x) O (8.5+z) The conductivity of the material is expressed in terms of composition dependence.

[0125] [ Fig.47 ] For Ba3W of Test Example 66 1.6 V 0.4 O 8.8 , which represents the oxygen partial pressure P(O2) dependence of the total conductivity.

[0126] [ Fig.48 ] For Ba3W of Test Example 66 1.6 V0.4 O 8.8 , for the conductivity in dry air and the conductivity in humid air, expressed in terms of temperature dependence.

[0127] [ Fig.49 ] represents the crystal structure of Ba3MoTiO8 of Test Example 68. Ba3MO (1-x) Ti (1+x) O (8+z) Also has a similar crystal structure.

[0128] [ Fig.50 ] represents Ba3MO of Test Examples 68 to 70 (1-x) Ti (1+x) O (8+z) Graph of the XRD pattern.

[0129] [ Fig.51 ] For Ba3MO of Test Examples 68 to 70 (1-x) Ti (1+x) O (8+z) The conductivity is expressed in terms of temperature dependence.

[0130] [ Fig.52 ] For Ba3MO of Test Example 69 1.1 Ti 0.9 O 8.1 , representing the P(O2) dependence of the total conductivity.

[0131] [ Fig.53 ] represents Ba7Ca2Mn5O of ​​Test Example 71 20 of the crystal structure.

[0132] [ Fig.54 ] represents the Ba7Ca2Mn5O 20 Graph of the XRD pattern.

[0133] [ Fig.55 ] For the Ba7Ca2Mn5O 20 The total conductivity is expressed in terms of temperature dependence.

[0134] [ Fig.56 ] represents Ba of Test Example 72 2.6 Ca 2.4 La4Mn4O 19 of the crystal structure.

[0135] [ Fig.57 ] represents Ba of Test Example 72 2.6 Ca 1.4 La4Mn4O 19 Graph of the XRD pattern.

[0136] [ Fig.58 ] For Ba of Test Example 72 2.6 Ca 1.4 La4Mn4O 19 The total conductivity is expressed in terms of temperature dependence.

[0137] [ Fig.59 ] represents the crystal structure of La2Ca2MnO7 of Test Example 73.

[0138] [ Fig.60 ] is a chart showing the XRD pattern of La2Ca2MnO7 of Test Example 73.

[0139] [ Fig.61 ] represents the Ba5M2Al2ZrO of Test Examples 74 to 80 13 The crystal structure of the material.

[0140] [ Fig.62 ] represents the Ba5M2Al2ZrO 13 Graph of the XRD pattern.

[0141] [ Fig.63 ] The temperature dependence of Ba5M2Al2ZrO 13 The total conductivity. DETAILED DESCRIPTION

[0142] Hereinafter, the solid electrolyte, electrolyte layer, and battery according to the present invention will be described with reference to embodiments thereof. However, the present invention is not limited to the following embodiments.

[0143] (Solid Electrolyte)

[0144] The solid electrolyte of this embodiment includes a hexagonal perovskite-related compound, which includes a substance represented by a specific general formula described later. Here, the so-called solid electrolyte is a material that conducts ions, and also includes materials that conduct both ions and (protons, electrons or their holes). The so-called hexagonal perovskite-related compound in this embodiment is a compound having a layered structure including a hexagonal perovskite unit or a compound having a structure similar to the compound.

[0145] The hexagonal perovskite-related compound in the solid electrolyte of this embodiment has a higher 20In particular, the composition is one in which the Nb concentration or the Mo concentration is increased or decreased, and / or the concentration of one or more elements forming cations is increased. The above-mentioned element forming a cation is preferably at least one element selected from the group consisting of Ag, Al, At, Au, Be, Bi, Br, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Hf, Hg, Ho, I, In, Ir, La, Li, Lu, Mg, Mn, Na, Nb, Nd, Ni, Np, Os, P, Pb, Pd, Po, Pr, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sm, Sn, Sr, Ta, Tb, Tc, Te, Ti, Tl, Tm, U, V, W, Xe, Y, Yb, Zn and Zr, and more preferably at least one element selected from the group consisting of W, V, Cr, Mn, Ge, Si and Zr.

[0146] Specifically, the solid electrolyte of the present embodiment includes a hexagonal perovskite-related compound represented by any one of the following general formulas (1) to (13).

[0147] Ba 7-α Nb (4-x-y) Mо (1+x) M y O (20+z) ···(1)

[0148] [In the formula (1), M is a cation of at least one element selected from the group consisting of Ag, Al, At, Au, Be, Bi, Br, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Hf, Hg, Ho, I, In, Ir, La, Li, Lu, Mg, Mn, Na, Nb, Nd, Ni, Np, Os, P, Pb, Pd, Po, Pr, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sm, Sn, Sr, Ta, Tb, Tc, Te, Ti, Tl, Tm, U, V, W, Xe, Y, Yb, Zn and Zr. α is the Ba deficiency, which is a value greater than 0 and less than 0.5, x is a value greater than -1.1 and less than 1.1, y is a value greater than 0 and less than 1.1, and z is the non-stoichiometric amount of oxygen, which is a value greater than -2.0 and less than 2.0. In formula (1), |x|+y≥0.01 is satisfied.]

[0149] Ba 7-α Nb (4-x―y) Mо (1+x) M y O (20+z) ···(2)

[0150] [In formula (2), M is a cation of at least one element selected from the group consisting of W, V, Cr, Mn, Ge, Si and Zr. α is the Ba deficiency, which represents a value greater than 0 and less than 0.5, x represents a value greater than -1.1 and less than 1.1, y represents a value greater than 0 and less than 1.1 and satisfies |x|+y≥0.01, and z represents the non-stoichiometric amount of oxygen, which represents a value greater than -2.0 and less than 2.0.]

[0151] 7B (4-x) Mо (1+x) O (20+z) ···(3)

[0152] [In formula (3), x represents a value of -1.1 to -0.01 or 0.01 to 1.1, and z represents the non-stoichiometric value of oxygen and represents a value of -2.0 to 2.0.]

[0153] 7B (4-y) MоM y O (20+z) ···(4)

[0154] [In formula (4), M is a cation of at least one element selected from the group consisting of V, Mn, Ge, Si and Zr. Y represents a value of 0.01 to 1.1, and z represents the non-stoichiometric value of oxygen, which represents a value of -2.0 to 2.0.]

[0155] Ba7Nb4M (1-y) M y O (20+z) ···(5)

[0156] [In formula (5), M is a cation of at least one element selected from the group consisting of V and Mn. z is the non-stoichiometric value of oxygen and represents a value of not less than -2.0 and not more than 2.0, and y represents a value of not less than 0.01 and not more than 1.1.]

[0157] 7B (4-y) MоCr y O (20+z) ···(6)

[0158] [In formula (6), z represents the non-stoichiometric amount of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.1.]

[0159] 7B (4-y) MoW y O (20+z) ···(7)

[0160] [In formula (7), z represents the non-stoichiometric amount of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.1.]

[0161] In the above formulas (1), (2) and (3), x is preferably 0.01 to 0.34, more preferably 0.18 to 0.22, and particularly preferably 0.19 to 0.21. When x is the above values, especially a value close to 0.20, the electrical conductivity at low temperatures becomes particularly high.

[0162] In the above formulas (1) and (2), y is preferably 0.06 to 0.24, more preferably 0.08 to 0.22, and particularly preferably 0.09 to 0.21. When y is the above values, particularly 0.1 to 0.2, the electrical conductivity at low temperatures becomes particularly high.

[0163] In the above formulas (4) and (5), y is preferably 0.06 to 0.14, more preferably 0.08 to 0.12, and particularly preferably 0.09 to 0.11. When y is the above values, especially a value close to 0.10, the electrical conductivity at low temperatures becomes particularly high.

[0164] In the above formula (6), y is preferably 0.16 to 0.24, more preferably 0.18 to 0.22, and particularly preferably 0.19 to 0.21. When y is the above values, especially a value close to 0.20, the electrical conductivity at low temperature becomes particularly high.

[0165] In the above formula (7), y is preferably 0.11 to 0.19, more preferably 0.13 to 0.17, and particularly preferably 0.14 to 0.16. When y is the above values, especially a value close to 0.15, the electrical conductivity at low temperature becomes particularly high.

[0166] In addition, it is also preferred to satisfy Ba3W (1-x) V (1+x) O (8.5+z) ···(8)

[0167] [In formula (8), x is preferably greater than or equal to -0.8 and less than or equal to 0.2, more preferably greater than or equal to -0.64 and less than or equal to -0.56, more preferably greater than or equal to -0.62 and less than or equal to -0.58, and more preferably greater than or equal to -0.61 and less than or equal to -0.59. If x is a value particularly close to -0.60, the electrical conductivity at low temperatures becomes particularly high. z is the non-stoichiometric property of oxygen, and represents a value greater than or equal to -1.0 and less than or equal to 1.0. ].

[0168] It is also preferred to satisfy Ba3MO (1-x) Ti (1+x)O (8+z) ···(9)

[0169] [In formula (9), x is preferably greater than or equal to -0.3 and less than or equal to 0.1, more preferably greater than or equal to -0.14 and less than or equal to -0.06, more preferably greater than or equal to -0.12 and less than or equal to -0.08, and more preferably greater than or equal to -0.11 and less than or equal to -0.09. If x is a value particularly close to -0.10, the electrical conductivity at low temperatures becomes particularly high. z is the non-stoichiometric property of oxygen, and represents a value greater than or equal to -0.1 and less than or equal to 0.3. ].

[0170] In addition, it is also preferred to satisfy Ba7Ca2Mn5O (20+z) ···(10)

[0171] [In formula (10), z is the non-stoichiometric amount of oxygen and represents a numerical value of -1.0 to 1.0. ]

[0172] In addition, it is also preferred to satisfy Ba 2.6 Ca 2.4 La4Mn4O (19+z) ···(11)

[0173] [In formula (11), z is the non-stoichiometric amount of oxygen and represents a numerical value of -1.0 to 1.0. ]

[0174] In addition, it is also preferred to satisfy La2Ca2MnO (7+z) ···(12)

[0175] [In formula (12), z is the non-stoichiometric amount of oxygen and represents a numerical value of -1.0 to 1.0. ]

[0176] In addition, it is also preferred to satisfy Ba5M2Al2ZrO (13+z) ···(13)

[0177] [In formula (13), M represents any one of Gd, Dy, Ho, Er, Tm, Yb or Lu. z represents the non-stoichiometric value of oxygen and represents a value of not less than -1.0 and not more than 1.0. ]

[0178] Among the hexagonal perovskite-related compounds of the solid electrolyte of the present embodiment, preferred compounds include, for example, Ba7Nb4MoO 20That is, when x in the general formula (3) is the excess amount of Mo x, x is a positive value, specifically, preferably a value of 0.01 to 0.50, further preferably a value of 0.01 to 0.34, more preferably 0.18 to 0.22, and particularly preferably 0.19 to 0.21. Specifically, in the case of Ba7Nb4MoO 20 When the excess amount x of Mo is 0.20, a particularly high electrical conductivity can be obtained.

[0179] In addition, regarding the above-mentioned Mo excess amount x, within the range of -1.1 to 1.1, it is also possible to appropriately adjust the amount that is easy to manufacture according to the raw materials used and the adjustment process. For example, the above-mentioned excess amount x can be a value of 0.01 to 0.20, or 0.09 to 0.11. Even at these values, high conductivity can be obtained. In addition, for example, even with respect to Ba7Nb4MoO 20 On the other hand, when the excess amount x of Mo is 0.10, high conductivity can be obtained.

[0180] In addition, Ba3W can be removed from the above formulas (1) to (13). (1-x) V (1+x) O (8.5+z) (x=-0.75, -0.60, -0.50, -0.40, -0.25, -0.10, -0.05, 0.0, 0.05, 0.10) and Ba 2.6 Ca 1.4 La4Mn4O 19 Select from the following compounds.

[0181] In addition, the a-axis length, b-axis length, and c-axis length of the lattice constants of the hexagonal perovskite-related compound in this embodiment are preferably For equations (2)-(7), the α angle, β angle, and γ angle (o) are respectively 5.35 < a < 6.56, 5.35 < b < 6.56, 15.14 < c < 18.52, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (8), they are respectively 5.23 < a < 6.4, 5.23 < b < 6.4, 18.96 < c < 23.19, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (9), they are respectively 5.34 < a < 6.54, 5.34 < b < 6.54, 19.12 < c < 23.39, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (10), they are respectively 5.23 < a < 6.41, 5.23 < b < 6.41, 46.23 < c < 56.51, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (11), they are respectively 8.85 < a < 10.83, 5.11 < b < 6.26, 14.07 < c < 17.21, 89 < α < 91, 100 < β < 104, 89 < γ < 91; for equation (12), they are respectively 5.05 < a < 6.19, 5.05 < b < 6.19, 15.57 < c < 19.03, 89 < α < 91, 89 < β < 91, 119 < γ < 121; for equation (13), they are respectively 5.35 < a < 6.55, 5.35 < b < 6.55, 22.23 < c < 27.18, 89 < α < 91, 89 < β < 91, 119 < γ < 121. Here, the lattice constant is a constant that defines the form and size of the unit lattice of this embodiment. α is the angle formed by the b-axis and the c-axis, β is the angle formed by the a-axis and the c-axis, and γ is the angle formed by the a-axis and the b-axis. In this embodiment, the lattice constant can be obtained using an XRD (X-ray diffraction) pattern. In addition, for the theoretically obtainable values of the lattice constant, they can also be obtained through structural optimization based on density functional theory (DFT) calculations.

[0182] A compound having such a lattice constant can achieve the effect of high conductivity at low temperatures.

[0183] In this embodiment, when a compound having the above respective conditions is used as an oxide ion (O 2- ) conductor or a solid electrolyte, it is assumed that an effective conductivity (oxide ion conductivity) is obtained. The so-called oxide ion (O 2-) conductor, which is a compound that conducts electricity by the conduction (migration) of oxide ions. In addition, the solid electrolyte using the compound of this embodiment is preferably used under a temperature condition of 300 to 1200°C, more preferably under a temperature condition of 300 to 1000°C, further preferably at 300°C or more and less than 700°C, and particularly preferably at 300 to 600°C. By using it under this temperature condition, it can be operated at a lower temperature than the conventional SOFC, so there are fewer restrictions on the devices and configurations required during operation, and a wide range of applications can be obtained.

[0184] Furthermore, the solid electrolyte using the compound of the present embodiment can also operate at a temperature higher than 600° C., which is similar to conventional SOFCs.

[0185] When the electrical conductivity of the solid electrolyte of this embodiment is measured at about 300°C, log[σ(Scm -1 The conductivity represented by )] is preferably -7 or more, more preferably higher than -5.0, and particularly preferably -3.5 or more. The conductivity at 300°C is sufficiently high, so that it has high conductivity at low temperatures and can be particularly suitable for batteries and other devices operating at low temperatures.

[0186] (Solid electrolyte layer)

[0187] In addition, the solid electrolyte of the present embodiment can be formed into a layer, or formed in a manner included in a layered structure, and used as a solid electrolyte layer. In addition to the solid electrolyte of the present embodiment, the solid electrolyte layer may also include other ion conductors, etc. In order to enable a battery using the solid electrolyte of the present embodiment to exert effective conductivity, in addition, in particular, to effectively operate as a low-temperature working battery described later, it is preferred to contain, for example, 50% by mass or more of the solid electrolyte layer, preferably 70% by mass or more of the solid electrolyte of the present embodiment containing a hexagonal perovskite-related compound.

[0188] (Battery containing a solid electrolyte or a solid electrolyte layer)

[0189] The solid electrolyte of the present embodiment or the electrolyte layer including the solid electrolyte can be used in a battery including the solid electrolyte. Among them, the solid electrolyte of the present embodiment can be particularly suitably used in a solid oxide fuel cell (SOFC) as described above.

[0190] In addition, the SOFC in the present embodiment refers to a battery in which electrodes and electrolytes constituting the battery are all formed of solids, and in particular, may be a battery in which ions between the electrodes are conducted as oxide ions.

[0191] The battery using the solid electrolyte in this embodiment or the electrolyte layer containing the solid electrolyte can be particularly suitable for low-temperature operation batteries. In this embodiment, the low-temperature operation battery is a battery that operates at 300 to 1200°C, preferably 300 to 1000°C, more preferably 300 to less than 700°C, and particularly preferably 300 to 600°C, as described above.

[0192] The battery in this embodiment includes, for example, an anode, a cathode, and the above-mentioned solid electrolyte layer interposed therebetween. The cathode and the solid electrolyte may form an integrated cathode-solid electrolyte layer assembly.

[0193] (Other uses of solid electrolytes)

[0194] In the past, perovskite-related compounds and solid electrolytes containing perovskite-related compounds showed high ion conductivity and were therefore widely used in batteries, sensors, ion concentrators, membranes used for ion separation and permeation, and catalysts, etc. The solid electrolyte of this embodiment can be used in the same manner as these. For example, the solid electrolyte of this embodiment can be used in other batteries, sensors, electrodes, electrolytes, oxygen concentrators, oxygen separation membranes, oxygen permeation membranes, oxygen pumps, catalysts, photocatalysts, electrical / electronic / communication equipment, energy / environment-related equipment, or optical equipment, etc., in addition to the above-mentioned solid oxide fuel cell (SOFC).

[0195] The solid electrolyte layer of the present embodiment described above can be used for a solid oxide fuel cell (SOFC), a sensor, an oxygen concentrator, an oxygen separation membrane, an oxygen permeable membrane, an oxygen pump, or the like.

[0196] The solid electrolyte of this embodiment can be used as an electrolyte of a gas sensor as a sensor, for example. By installing a sensing electrode corresponding to the gas to be detected on the electrolyte, a gas sensor or a gas detector can be formed. For example, when a sensing electrode containing carbonate is used, a carbon dioxide gas sensor can be obtained, when a sensing electrode containing nitrate is used, a NOx sensor can be obtained, and when a sensing electrode containing sulfate is used, a SOx sensor can be obtained. In addition, by combining an electrolytic cell, a capture device or a decomposition device for NOx and / or SOx contained in exhaust gas can be formed.

[0197] Furthermore, the solid electrolyte of the present embodiment can be used as an adsorbent or adsorption separation agent for ions or the like, or various catalysts, or the like.

[0198] In addition, the solid electrolyte of this embodiment may also function as an activator for various rare earths in the ion conductor to form luminescence centers (color centers). In this case, it can be used as a wavelength changing material or the like.

[0199] In addition, the solid electrolyte of the present embodiment may become a superconductor by being doped with electron carriers or hole carriers.

[0200] The solid electrolyte of this embodiment can also be used as an ion conductor, and inorganic compounds that are colored or discolored by the insertion and removal of conductive ions are attached to the surface of the solid electrolyte, and a light-transmitting electrode such as ITO is further formed thereon, thereby making a fully solid electrochromic element. By using the fully solid electrochromic element, an electrochromic display with memory characteristics that suppresses power consumption can be provided.

[0201] Example

[0202] (Sample synthesis)

[0203] (Test Examples 1 to 21)

[0204] The compounds shown in the "Composition" of Test Examples 1 to 21 in Table 1 were prepared by a solid phase reaction method. It should be noted that in the composition of Table 1, the oxidation number of Ba is assumed to be +2, the oxidation number of Nb is assumed to be +5, the oxidation number of Mo is assumed to be +6, the oxidation number of oxygen O is assumed to be -2, the oxidation number of W is assumed to be +6, the oxidation number of V is assumed to be +5, the oxidation number of Cr is assumed to be +6, the oxidation number of Ge is assumed to be +4, the oxidation number of Si is assumed to be +4, and the oxidation number of Zr is assumed to be +4, and the oxygen amount calculated from the electroneutrality condition is shown, but the non-stoichiometric amount z of oxygen depends on the molar ratio of cations, temperature, oxygen partial pressure, synthesis method and thermal history, so the oxygen amount (20+z) is not limited to the numerical value shown. As starting materials, BaCO3, Nb2O5, MoO3, WO3, V2O5, Cr2O3, GeO2, SiO2, and ZrO2 were used. After the starting raw materials were dried in an electric furnace at 250-300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 30 minutes to 2 hours. The resulting mixture was pre-calcined at 900°C in the atmosphere for 10 to 12 hours in an electric furnace. For the pre-calcined mixture, wet mixing and grinding using ethanol and dry mixing and grinding were repeated for 30 minutes to 2 hours using an agate mortar. Using a uniaxial press, pressurized at 62 to 150 MPa, the mixture was formed into cylindrical particles with a diameter of 10 to 20 mm. The resulting particles were placed in an electric furnace and sintered at 1100°C for 24 hours in the atmosphere. As a result, particles as sintered bodies were obtained. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was pulverized with a tungsten carbide (WC) pulverizer for 20 minutes and then ground with an agate mortar for 30 minutes to 1 hour.

[0205] For the compounds having the compositions of Test Examples 1 and 6, high-density samples were prepared by applying hydrostatic pressure once before sintering. On the other hand, the samples that were sintered without hydrostatic pressure treatment before sintering were called low-density samples. The theoretical density of each sample was set to 5.85 g / cm 3 , calculate the following relative density = 100×(density) / (theoretical density)%.

[0206] The density of the high-density sample of Test Example 1 is 5.2725 g / cm 3 , the relative density is 90.1%.

[0207] The density of the low-density sample of Test Example 1 is 3.9659 g / cm 3 , the relative density is 67.8%.

[0208] The density of the high-density sample of Test Example 6 is 5.5951 g / cm 3 , the relative density is 95.6%.

[0209] The density of the low-density sample of Test Example 6 is 3.9165 g / cm 3 , the relative density is 66.9%.

[0210] For each test example, XRD measurement was performed using a diffraction device Bruker D8. The obtained XRD pattern was indexed using DICVOL06 to determine the lattice constant. The XRD pattern of Test Example 1 is shown in Figure 1 middle.

[0211] The results of XRD measurement for Test Examples 2 to 21 are shown in FIG. Figures 2 to 21 The lattice constants were determined from the obtained XRD patterns. Table 1 shows the lattice constants (a, b, c, α, β, γ) and lattice volumes V of Test Examples 1 to 21.

[0212] [Table 1]

[0213]

[0214] (Total conductivity measurement)

[0215] The conductivity of each test example in Table 1 except for Test Example 21 was measured by a DC four-probe method. The particle size of the sample prepared in the above (Sample Synthesis) was reduced using a ball mill and then uniaxially pressed to form a The particles were sintered to produce a sample for conductivity measurement. Four platinum wires were wound around the sintered body for total conductivity measurement using the DC four-terminal method. Platinum paste was applied to the platinum wires to make the sample and the platinum wires adhere closely. In order to remove the organic components contained in the platinum or gold paste, it was heated at 900°C for 1 hour. For each test example, the measured conductivity is shown in Tables 2 to 9. In addition, in the compositions of Tables 2 to 9, the oxidation number of Ba is assumed to be +2, the oxidation number of Nb is assumed to be +5, the oxidation number of Mo is assumed to be +6, the oxidation number of oxygen O is assumed to be -2, the oxidation number of W is assumed to be +6, the oxidation number of V is assumed to be +5, the oxidation number of Cr is assumed to be +6, the oxidation number of Ge is assumed to be +4, the oxidation number of Si is assumed to be +4, and the oxidation number of Zr is assumed to be +4, and the oxygen amount calculated under the condition of electrical neutrality is shown, but the non-stoichiometric amount z of oxygen depends on the molar ratio of cations, temperature, oxygen partial pressure, synthesis method and thermal history, etc., and therefore the oxygen amount (20+z) is not limited to the numerical value stated.

[0216] [Table 2]

[0217]

[0218] [Table 3]

[0219]

[0220] [Table 4]

[0221]

[0222] [Table 5]

[0223]

[0224] [Table 6]

[0225]

[0226] [Table 7]

[0227]

[0228] [Table 8]

[0229]

[0230] [Table 9]

[0231]

[0232] From Tables 2 to 9, in any of Test Examples 2 to 20, log [σ (Scm -1)] The conductivity is in the range of -7.0 to -1.0. The conductivity at 300°C or according to the above data and Figures 22 to 26 By extrapolation, we can obtain the value from log[σ(Scm -1 )] is -6.2 or more in Test Examples 2 to 20. Therefore, Test Examples 2 to 20 can all obtain high conductivity at low temperatures. In addition, the conductivity at 300°C is higher than -5.0 in Test Examples 2, 3, 5, 6 (high density), 8 to 11, 16 and 20. Among all the test examples, the test example with the highest conductivity near 300°C is Test Example 6, and the conductivity log [σ (Scm) at 280°C is -6.2 or more in Test Examples 2 to 20. -1 )] has a value of -3.7. In addition, the conductivity of Test Example 21 was not measured, but it is believed that it is similar to that of Ba7Nb in Test Example 20. 4.05 MO 0.95 O 19.975 Electrical (ionic) conduction is also shown.

[0233] The conventionally used YSZ (Comparative Example 1), Test Example 1 (Ba7Nb4MoO 20 ) (high density) and Test Example 6 (Ba7Nb 3.9 MO 1.1 O 20.05 The conductivity σ of each (high density) will be expressed as log[σ(Scm -1 )] as the vertical axis, and the absolute temperature T obtained from the temperature of the table is 1000T -1 / K -1 The graph (Arrhenius curve) drawn for the horizontal axis is shown in Fig. 22 middle.

[0234] Depend on Fig. 22 It can be seen that the conductivity increases with the increase in temperature. At 600°C, the conductivity of the Ba7Nb4MoO 20 The conductivity σ of Test Example 6 in which the excess amount x of Mo was set to 0.10 was 5.5 times higher than that of Test Example 6. The conductivity was improved by making the amount of Mo excessive.

[0235] In the conventional test example 1, at 600°C, log[σ(Scm -1 )] = -2.7. In Test Example 6, in which the Mo excess amount x is 0.10, at a temperature of 590°C or below, log[σ(Scm -1 )] is higher than that of YSZ and Test Example 1, indicating that the electrical conductivity is higher than that of the electrolytes used in the past.

[0236] In addition, Ba7Nb4MoO in which the excess Mo amount x in the general formula (7) is 0.02 to 0.10 20The Arrhenius curve of the conductivity is shown in Fig.23 In the Ba7Nb4MoO 20 The Arrhenius curve of the conductivity is shown in Fig.24 middle. Fig.23 and 24 For comparison, the Ba7Nb4MoO 20 The above-mentioned test examples 1 (high density, low density), 2, 3, 4, 5, 6 (high density, low density), 7, 8, 9 and 10 correspond to the Mo excess amount x (Ba7Nb (4-x) MO (1+x) O (20+z) The x) in is 0 (high density, low density), 0.02, 0.04, 0.06, 0.08, 0.10 (high density, low density), 0.12, 0.14, 0.16 and 0.18.

[0237] The electrical conductivity of the high-density samples of Test Example 1 (x=0) and Test Example 6 (x=0.10) is higher than that of the low-density samples at any temperature.

[0238] The samples with Mo excess x in the range of 0.02 to 0.18 (Test Examples 2 to 10) and Ba7Nb4MoO 20 All of them showed high conductivity compared with the low-density sample of (Test Example 1). The high-density sample with Mo excess x of 0.10 had the highest conductivity, and maintained high conductivity even at a low temperature of about 300°C.

[0239] In addition, Ba7Nb4MoO2 with a doping amount y of 0.1 of W, V (partially replacing Mo), V (partially replacing Nb), Cr, Si, Ge, and Zr 20 The Arrhenius curve of the conductivity (y=0.10 in the general formulas (4) to (7)) is shown in Fig.25 The above-mentioned test examples 11, 12, 13, 14, 17, 18 and 19 correspond to the results of compounds doped with W (partially replacing Nb), V (partially replacing Mo), V, Cr, Ge, Si and Zr (partially replacing Nb), respectively. Among these compounds, the conductivity of the compound doped with W is the highest in all the temperature ranges drawn. In other test examples, the conductivity of the compounds doped with Cr and V (partially replacing Mo) is high at high temperatures, but if 1000T -1 / K -1 When the temperature is 1.4 or more, that is, a low temperature of about 441° C. or less, the conductivity of the compound doped with Si increases.

[0240] In addition, Ba7Nb4MoO 20 (Ba7Nb where y=0.10 to 0.30 in the general formula (10) (4-y) MоCr y O (20+z) The Arrhenius curve of the conductivity of Fig.26 The above-mentioned test examples 14, 15, and 16 correspond to samples with doping amounts y of 0.10, 0.20, and 0.30, respectively. Ba7Nb4MoO 20 The conductivity of (y=0.10~0.30) is similar to that of Ba7Nb4MoO 20 In contrast, it becomes higher at 800°C or below.

[0241] (Oxygen partial pressure dependence of total conductivity)

[0242] For Test Example 1, the oxygen partial pressure dependence of the total conductivity was measured. The sample was prepared in the same manner as described above (total conductivity measurement). In addition, oxygen O2 gas, nitrogen N2 gas, or N2 / H2 mixed gas was used to control the oxygen partial pressure.

[0243] In the oxygen partial pressure range 3.5×1 -25 Determination of oxygen partial pressure dependence of total conductivity at 0.2 atm and 900°C. Monitor oxygen partial pressure using an oxygen sensor located downstream of the device. Control oxygen partial pressure by mixing a small amount of N2 / H2 mixed gas into nitrogen.

[0244] The oxygen partial pressure log [P(O2) / atm] on the horizontal axis and the measured conductivity log [σ(Scm -1 )] as the vertical axis is plotted in Fig. 27 The total conductivity does not depend on the oxygen partial pressure and takes a basically constant value, which strongly suggests that oxide ions are the dominant carriers in the electrical conduction of the compound of Test Example 1. Test Examples 2 to 21 having similar crystal structures are also considered to be compounds in which oxide ions are the dominant carriers.

[0245] (Evaluation of oxide ion transmission rate)

[0246] In Test Example 6, in order to determine the oxide ion transmission rate, an electromotive force was measured using an oxygen concentration cell using air and N2 / O2 mixed gas. The particle size of the sample prepared by the above (sample synthesis) was reduced using a ball mill and then uniaxially pressed into The particles were subjected to hydrostatic pressure. The high-density sample of Test Example 6 for electromotive force measurement was sintered at 1200°C for 12 hours. The surface of the sample was cut with diamond slurry to make it smooth. The relative density of the particles of Test Example 6 is 96.0%. A Pt paste with a diameter of about 10 mm was applied to the center of the particle, and heated at 1000°C for 1 hour to remove the organic components contained in the platinum paste. The platinum paste was bonded to the platinum electrode using an instant adhesive, and the alumina tube was bonded to the glass seal and the sample using an instant adhesive, and the platinum electrode was installed. The pressure foot used in the measurement used an alumina clip. In order to ensure the tightness of the glass seal, after heating at 1000°C for 1 hour, the transmission rate of the oxide ions of Test Example 6 was determined at 800°C and 900°C by electromotive force measurement using an oxygen concentration cell.

[0247] The results of the electromotive force measurement of the oxygen concentration difference cell of Test Example 6 at temperatures of 800°C and 900°C are plotted with electromotive force / mV as the vertical axis and oxygen partial pressure log [P(O2) / atm] as the horizontal axis. Fig.28 and Fig.29 The measured values ​​obtained an electromotive force close to the theoretical value, and in particular, the oxide ion transmission rate at 900°C was 94%, indicating that oxide ions are the dominant carriers in the electrical conduction of the compound of Test Example 6, and the compound of Test Example 6 is an oxide ion conductor. It is believed that Test Examples 1 to 5 and 7 to 21 having similar crystal structures also show the same transmission rate.

[0248] (Structural optimization using density functional theory calculations)

[0249] For Ba7Nb3MоMO 20 Structural optimization calculations based on density functional theory were performed. Here, M is a cation of at least one element selected from the group consisting of Ag, Al, At, Au, Be, Bi, Br, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Hf, Hg, Ho, I, In, Ir, La, Li, Lu, Mg, Mn, Mo, Na, Nb, Nd, Ni, Np, Os, P, Pb, Pd, Po, Pr, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sm, Sn, Sr, Ta, Tb, Tc, Te, Ti, Tl, Tm, U, V, W, Xe, Y, Yb, Zn, and Zr. In addition, for Ba7Nb3Mо2O 20Structural optimization calculations were performed. Density functional theory calculations using generalized gradient approximation and PBE functionals were performed using the program VASP. The results of the lattice constants obtained by structural optimization are shown in Tables 10 to 12 and Tables 33 to 36. In any composition, the optimized structure maintains the crystal structure of the original hexagonal perovskite-related compound, showing the possibility of synthesizing these compositions. It is believed that these compositions also show oxide ion conduction.

[0250] [Table 10]

[0251]

[0252] [Table 11]

[0253]

[0254] [Table 12]

[0255]

[0256] (Test Examples 22 to 83)

[0257] The compounds shown in the "Compositions" of Test Examples 22 to 41 shown in Table 13, Test Examples 42 to 61 shown in Table 14, and Test Examples 62 to 83 shown in Table 15 were prepared according to the following procedure. In the compositions of Tables 13 to 15, the oxidation number of Ba was assumed to be +2, the oxidation number of Nb was assumed to be +5, the oxidation number of Mo was assumed to be +6, the oxidation number of oxygen O was assumed to be -2, the oxidation number of W was assumed to be +6, the oxidation number of V was assumed to be +5, the oxidation number of Cr was assumed to be +6, the oxidation number of Ge was assumed to be +4, the oxidation number of Si was assumed to be +4, the oxidation number of Zr was assumed to be +4, the oxidation number of Ti was assumed to be +4, and the oxidation number of Al was assumed to be +3, the oxidation number of Gd is assumed to be +3, the oxidation number of Dy is assumed to be +3, the oxidation number of Er is assumed to be +3, the oxidation number of Ho is assumed to be +3, the oxidation number of Tm is assumed to be +3, the oxidation number of Yb is assumed to be +3, and the oxidation number of Lu is assumed to be +3, and the oxygen amount calculated under the condition of electrical neutrality is shown, but the non-stoichiometric amount z of oxygen depends on the molar ratio of cations, temperature, oxygen partial pressure, synthesis method and thermal history, etc., and therefore the oxygen amount (20+z) is not limited to the stated numerical value.

[0258] (Test Examples 22 to 58 and 81 to 83)

[0259] The compounds shown in the "Composition" of Test Examples 22 to 41 of Table 13, Test Examples 42 to 58 of Table 14, and Test Examples 81 to 83 of Table 15 were prepared by a solid phase reaction method. As starting materials, BaCO3, Nb2O5, MoO3, WO3, V2O5, Cr2O3, MnO2, GeO2, SiO2, and ZrO2 were used. After the starting materials were dried in an electric furnace at 250 to 300°C for 12 hours, they were weighed using an electronic balance so that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 30 minutes to 2 hours. The obtained mixture was pre-calcined at 900°C in an electric furnace under the atmosphere for 10 to 12 hours. For the pre-calcined mixture, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 30 minutes to 2 hours using an agate mortar. The mixture was formed into cylindrical particles with a diameter of 10 to 20 mm by applying pressure at 62 to 150 MPa using a uniaxial press. The obtained particles were placed in an electric furnace and sintered at 1100° C. for 24 hours in the atmosphere. As a result, particles as sintered bodies were obtained. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed with a tungsten carbide (WC) pulverizer for about 20 minutes, and then ground with an agate mortar for 30 minutes to 1 hour.

[0260] (Test Examples 59 to 67)

[0261] The compounds shown in the "Composition" of Test Examples 59 to 61 of Table 14 and Test Examples 62 to 67 of Table 15 were prepared by a solid phase reaction method. BaCO3, WO3, and V2O5 were used as starting materials. After the starting materials were dried in an electric furnace at 300°C for 12 hours in advance, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 1 hour. The obtained mixture was pre-calcined at 950°C in the atmosphere in an electric furnace. The pre-calcined mixture was repeatedly mixed and ground for 1 hour in a dry manner and a wet manner using ethanol using an agate mortar. Using a uniaxial press, the mixture was pressurized at 150MPa to form cylindrical particles with a diameter of 10mm. The obtained particles were placed in an electric furnace and sintered at 1020°C in the atmosphere for 24 hours. As a result, particles as sintered bodies were obtained. The obtained sintered body was used to measure the electrical conductivity. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was pulverized with a tungsten carbide (WC) pulverizer for about 20 minutes and then ground with an agate mortar for about 1 hour.

[0262] (Test Examples 68 to 70)

[0263] The compounds shown in the "Composition" of Test Examples 68 to 70 in Table 15 were prepared by a solid phase reaction method. BaCO3, TiO2, and MoO3 were used as starting materials. After the starting materials were dried in an electric furnace at 250 to 300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 30 minutes. The resulting mixture was pre-calcined at 900°C for 12 hours in an electric furnace under atmosphere. The pre-calcined mixture was repeatedly mixed and ground in a dry manner and in a wet manner using ethanol for about 1 hour using an agate mortar. Using a uniaxial press, the mixture was pressurized at 150 MPa to form cylindrical particles with a diameter of 20 mm. The resulting particles were placed in an electric furnace and sintered at 1100°C for 24 hours in atmosphere. The obtained sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar. Using a uniaxial press, pressurized at 150MPa, the mixture was formed into cylindrical particles with a diameter of 5mm. The obtained particles were placed in an electric furnace and sintered at 1100°C for 12 hours under atmosphere. As a result, particles as a sintered body were obtained. The obtained sintered body was used to measure the electrical conductivity. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar.

[0264] (Test Example 71)

[0265] The compound shown in the "Composition" of Test Example 71 in Table 15 was prepared by a solid phase reaction method. BaCO3, MnO2, and CaCO3 were used as starting materials. After the starting materials were dried in an electric furnace at 250-300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for about 1 hour. The obtained mixture was pre-calcined at 900°C for 12 hours in an electric furnace under atmosphere. The pre-calcined mixture was repeatedly subjected to dry mixing and grinding and wet mixing and grinding using ethanol for 30 minutes using an agate mortar. Using a uniaxial press, the mixture was pressurized at 150MPa to form cylindrical particles with a diameter of 20mm. The obtained particles were placed in an electric furnace and sintered at 1200°C for 12 hours in atmosphere. The obtained sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar. Using a uniaxial press, pressurized at 150MPa, the mixture was formed into cylindrical particles with a diameter of 5mm. The obtained particles were placed in an electric furnace and sintered at 1400°C for 24 hours under atmosphere. As a result, particles as a sintered body were obtained. The obtained sintered body was used to measure the electrical conductivity. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar.

[0266] (Test Example 72)

[0267] The compound shown in the "Composition" of Test Example 72 in Table 15 was prepared by a solid phase reaction method. BaCO3, MnO2, La2O3, and CaCO3 were used as starting materials. After the starting materials were dried in an electric furnace at 250-300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for about 1 hour. The resulting mixture was pre-calcined at 900°C in the atmosphere for 10 hours in an electric furnace. The pre-calcined mixture was repeatedly mixed and ground in a dry manner and in a wet manner using ethanol for about 1 hour using an agate mortar. Using a uniaxial press, the mixture was pressurized at 150MPa to form cylindrical particles with a diameter of 5mm. The resulting particles were placed in an electric furnace and sintered at 1200°C for 12 hours in the atmosphere. The obtained sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar. Using a uniaxial press, pressurized at 150MPa, the mixture was formed into cylindrical particles with a diameter of 5mm. The obtained particles were placed in an electric furnace and sintered for 12 hours at 1200°C under atmosphere. As a result, particles as a sintered body were obtained. The obtained sintered body was used to measure electrical conductivity. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed for 20 minutes using a pulverizer made of tungsten carbide (WC), and then ground for about 1 hour using an agate mortar.

[0268] (Test Example 73)

[0269] The compound shown in the "Composition" of Test Example 73 of Table 15 was prepared by a solid phase reaction method. As starting materials, La2O3, MnO2, and CaCO3 were used. After the starting materials were dried in an electric furnace at 250-300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for about 1 hour. The obtained mixture was pre-calcined at 900°C in the atmosphere in an electric furnace. The pre-calcined mixture was repeatedly mixed and ground in a dry manner and in a wet manner using ethanol for about 1 hour using an agate mortar. Using a uniaxial press, the mixture was pressurized at 150MPa to form cylindrical particles with a diameter of 5mm. The obtained particles were placed in an electric furnace and sintered at 1200°C for 12 hours in the atmosphere. As a result, particles as sintered bodies were obtained. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed with a tungsten carbide (WC) grinder for 20 minutes and then ground with an agate mortar for about 1 hour. This compound also has a crystal structure similar to that of the compounds of Test Examples 1 to 21, and is therefore considered to have oxide ion conductivity.

[0270] (Test Examples 74 to 80)

[0271] The compounds shown in the "Composition" of Test Examples 74 to 80 in Table 15 were prepared by a solid phase reaction method. As starting materials, BaCO3, Al2O3, ZrO2, Gd2O3, Dy2O3, HO2O3, Er2O3, TM2O3, Yb2O3, and Lu2O3 were used. After the starting materials were dried in an electric furnace at 300°C for 12 hours, they were weighed using an electronic balance in such a way that the molar ratio of cations became the target chemical composition. Using an agate mortar, dry mixing and grinding and wet mixing and grinding using ethanol were repeated for 30 minutes. The resulting mixture was pre-calcined at 900°C for 10 hours in an electric furnace under atmosphere. The pre-calcined mixture was dry mixed and ground for 30 minutes using an agate mortar. Using a uniaxial press, the mixture was pressurized at about 50 MPa to form cylindrical particles with a diameter of 20 mm. The obtained pellets were placed in an electric furnace and sintered at 1600° C. for 12 hours in the atmosphere to obtain a sintered body. The obtained sintered body was used to measure the electrical conductivity. In order to evaluate the generated phase of the obtained compound by X-ray diffraction (XRD), a part of the sintered body was crushed with a tungsten carbide (WC) pulverizer for 20 minutes and then ground with an agate mortar for about 30 minutes.

[0272] In each table, the lattice constant and lattice volume V of Test Examples 22 to 83 are also shown. In addition, for some of the test examples, the activation energy E of the conductivity estimated from the temperature dependence of the total conductivity is also shown. a (eV) The transmission rate of Test Example 27 at 900°C was 100%.

[0273] Fig.30 The Ba7Nb4MoO used in Test Example 22 is shown. 20 In this figure, the space group is P-3m1 (No.164) and the lattice constant is As Ba7Nb4MoO 20 Test Examples 23 to 58 and 81 to 83 of the series materials also have similar crystal structures. Fig.31 and Fig.32 To show Ba7Nb (4-x) MO (1+x) O (20+z) Graph of the XRD pattern. Fig.31 The measurement graphs for x=0, 0.02, 0.04, 0.06, 0.08, and 0.1 are shown. Fig.32 The measurement graphs for x=0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.25, 0.3, 0.4, and 0.5 are shown.(4-x) MO (1+x) O (20+z) The conductivity of Fig.33 The temperature dependence is plotted for each value of x in Fig.34 The values ​​for each temperature in are plotted as composition dependent.

[0274] Fig.35 Indicates the Ba7Nb used in Test Examples 40 to 44 and 46. (4-y) MоCr y O (20+z) The XRD pattern of Ba7Nb is shown in Figure 2. The XRD patterns of Ba7Nb are shown in Figure 2 when x=0.1, 0.2, 0.25, 0.3, 0.4, and 0.5. (4-x) MO (1+x) O (20+z) The conductivity of Fig.36 Plotted as a function of temperature.

[0275] Fig.37 In the case of Ba7Nb used in Test Examples 22, 40 to 44, and 46, (4-y) MоCr y O (20+z) The conductivity of the material is plotted as a composition dependency.

[0276] Fig.38 Indicates the Ba7Nb used in Test Examples 52 to 58 and 81 to 83. (4-y) MoW y O (20+z) Graph of the XRD pattern. Fig.39 For Ba7Nb (4-y) MoW y O (20+z) The total conductivity is expressed in terms of temperature dependence. Fig.40 For Ba7Nb (4-y) MoW y O (20+z) The overall conductivity is expressed in terms of composition dependence.

[0277] Fig.41 This is to show Ba7Nb as another solid solution used in Test Examples 38, 39, 45, and 47 to 51. 3.9 MоM 0.1 O (20+z) (M is V, Mn, Ge, Si or Zr), Ba7Nb4Mо 0.9 M 0.1 O (20+z) (M is V or Mn) and Ba7Nb 4.05 Mо 0.95 O (20+z) Graph of the XRD pattern. Fig.42 In the above, the electrical conductivity of the solid solution used in Test Examples 38, 39, and 47 to 50 is expressed in terms of temperature dependence.

[0278] Fig.43 Ba3WVO used in Test Examples 59 to 67 8.5 The crystal structure of the material is considered to be 8.5 The system has the crystal structure of (a), but the crystal structures of Figures (b) and (c) are proposed based on the analysis results. In these figures, the space group is R-3m (No.166) and the lattice constant is Fig.44 To represent Ba3W (1-x) V (1+x) O (8.5+z) Graph of the XRD pattern. Fig.45 In the equation, the conductivity is expressed in terms of temperature dependence. Fig.46 In the above, the conductivity is expressed in terms of composition dependence. The conductivity increases with increasing temperature. At 600°C, the conductivity is similar to that of Ba3WVO of Test Example 59. 8.5 The conductivity of Ba3W in Test Example 66 is compared with 1.6 V 0.4 O 8.8 The conductivity σ of Ba3WVO is 85 times higher, which shows that the conductivity is improved by making the W content excessive. 8.5 The same is considered to be true for Test Examples 59 to 65 and 67 of the series material.

[0279] Fig.47 In the test example 66, Ba3W 1.6 V 0.4 O 8.8 , indicating the P(O2) dependence of the conductivity. Since there is a region where the total conductivity takes a nearly constant value regardless of the oxygen partial pressure, it is suggested that in the electrical conduction of the compound of Test Example 66, oxide ions are the dominant carriers in this region. Fig.48 For Ba3W 1.6 V 0.4 O 8.8 , indicating the conductivity in dry air and the conductivity in humid air. No change in the total conductivity was confirmed in the measurement of humid air and dry air for Test Example 66, which strongly suggests that proton conduction did not occur in Test Example 66. 8.5 The same is considered to be true for Test Examples 59 to 65 and 67 of the series material.

[0280] Fig.49The crystal structure of the Ba3MoTiO8 material used in Test Examples 68 to 70 is shown. In this figure, the space group is R-3m (No. 166) and the lattice constant is Fig.50 To represent Ba3MO (1-x) Ti (1+x) O (8+z) Graph of the XRD pattern.

[0281] In addition, Ba3MO with Ti excess x of -0.1 and -0.2 1.1 Ti 0.9 O 8.1 and Ba3MO 1.2 Ti 0.8 O 8.2 The temperature dependence of the conductivity is shown in Fig.51 The temperature dependence of the conductivity of Ba3MoTiO8 with a Mo excess x of 0.0 in the test example of this embodiment is also shown. The samples with Mo excess x in the range of -0.1 and -0.2 all show high conductivity compared with the sample of Ba3MoTiO8 with x of 0.0 (Test Example 68). Below 620°C, the conductivity of the sample with Mo excess x of -0.1 is the highest, and the high conductivity is maintained even at a low temperature of about 300°C.

[0282] (Oxygen partial pressure dependence of total conductivity)

[0283] For Test Example 69, the oxygen partial pressure dependence of the total conductivity was measured. The oxygen partial pressure log [P(O2) / atm] relative to the horizontal axis was plotted as the measured conductivity log [σ(Scm -1 )] as the vertical axis is plotted in the figure Fig.52 The total conductivity does not depend on the oxygen partial pressure and takes a substantially constant value, which strongly suggests that oxide ions are the dominant carriers in the electrical conduction of the compound of Test Example 69. The same is believed to be true for Test Examples 68 and 70, which are the same Ba3MoTiO8-based materials.

[0284] Fig.53 The Ba7Ca2Mn5O used in Test Example 71 is shown. 20 The crystal structure of the material of the system. In this figure, the space group is R-3m (No.166), the lattice constant Fig.54 To represent Ba7Ca2Mn5O 20 Graph of the XRD pattern. Fig.55 For Ba7Ca2Mn5O 20 The total conductivity is expressed in terms of temperature dependence.

[0285] Fig.56Ba used in Test Example 72 2.6 Ca 1.4 La4Mn4O 19 The crystal structure of the material. 2.6 Ca 1.4 La4Mn4O 19 The space group is C2 / m (No.12), and the lattice constant is β=102.09°. Fig.57 To represent Ba 2.6 Ca 1.4 La4Mn4O 19 Graph of the XRD pattern. Fig.58 In, will Ba 2.6 Ca 1.4 La4Mn4O 19 The total conductivity is expressed in terms of temperature dependence.

[0286] Fig.59 The crystal structure of the La2Ca2MnO7 material used in Test Example 73 is shown. In this figure, the space group is R-3m (No. 166) and the lattice constant is Fig.60 This is a chart showing the XRD pattern of La2Ca2MnO7.

[0287] Fig.61 In the figure, Ba5M2Al2ZrO used in Test Examples 74 to 80 is shown. 13 The crystal structure of the material of the system. In this figure, the space group is P63 / mmc (No.194) and the lattice constant is Fig.62 To represent Ba5M2Al2ZrO 13 Graph of XRD patterns of (M is Gd, Dy, Er, Ho, Tm, Yb, Lu). Fig.63 The Ba5M2Al2ZrO 13 The total conductivity of the test example 76 is expressed as temperature dependence. For the test example 76, the total conductivity in dry air is also expressed as temperature dependence. Since the conductivity decreases in dry air, it is suggested that the test example 76 shows proton conduction. 13 The same is considered to be true for Test Examples 74, 75, and 77 to 80, which are materials.

[0288] [Table 13]

[0289]

[0290] [Table 14]

[0291]

[0292] [Table 15]

[0293]

[0294] The results of the test examples in which the electrical conductivity was measured in Test Examples 22 to 83 are shown in Tables 16 to 32. In the compositions in Tables 16 to 32, the oxidation number of Ba is assumed to be +2, the oxidation number of Nb is assumed to be +5, the oxidation number of Mo is assumed to be +6, the oxidation number of oxygen O is assumed to be -2, the oxidation number of W is assumed to be +6, the oxidation number of V is assumed to be +5, the oxidation number of Cr is assumed to be +6, the oxidation number of Ge is assumed to be +4, the oxidation number of Si is assumed to be +4, the oxidation number of Zr is assumed to be +4, the oxidation number of Ti is assumed to be +4, the oxidation number of Al is assumed to be +3, The oxidation number of Gd is assumed to be +3, the oxidation number of Dy is assumed to be +3, the oxidation number of Er is assumed to be +3, the oxidation number of Ho is assumed to be +3, the oxidation number of Tm is assumed to be +3, the oxidation number of Yb is assumed to be +3, and the oxidation number of Lu is assumed to be +3, and the oxygen amount calculated under the condition of electrical neutrality is shown. However, the non-stoichiometric amount z of oxygen depends on the molar ratio of cations, temperature, oxygen partial pressure, synthesis method and thermal history, etc., and therefore the oxygen amount (20+z) is not limited to the numerical value shown.

[0295] [Table 16]

[0296]

[0297] [Table 17]

[0298]

[0299] [Table 18]

[0300]

[0301] [Table 19]

[0302]

[0303] [Table 20]

[0304]

[0305] [Table 21]

[0306]

[0307] [Table 22]

[0308]

[0309] [Table 23]

[0310]

[0311] [Table 24]

[0312]

[0313] [Table 25]

[0314]

[0315] [Table 26]

[0316]

[0317] [Table 27]

[0318]

[0319] [Table 28]

[0320]

[0321] [Table 29]

[0322]

[0323] [Table 30]

[0324]

[0325] [Table 31]

[0326]

[0327] [Table 32]

[0328]

[0329] In the test examples shown in Tables 16 to 32, log[σ(Scm -1 )] are all within the range of -7.0 to -1.0. For example, Test Example 32 has a conductivity of -3.4 to -2.0 at 306 to 606°C, showing high conductivity at low temperatures.

[0330] (Calculation example)

[0331] For Ba7Nb4MoO 20 , design a structure in which part of Nb is replaced by other elements, and calculate the a-axis length, b-axis length, and c-axis length of the lattice constant Angle α, angle β, angle γ (o). (Test Examples 84 to 152, Tables 33 to 36) [Table 33]

[0332]

[0333] [Table 34]

[0334]

[0335] [Table 35]

[0336]

[0337] [Table 36]

[0338]

[0339] Regarding the compounds having the compositions of Test Examples 84 to 152, the optimized structures according to the calculation examples also maintain the crystal structure of the original hexagonal perovskite-related compounds, indicating the possibility of synthesizing these compositions. As with Test Examples 1 to 83, it is believed that by using these compositions also in solid electrolytes, for example, excellent properties are exhibited in terms of electrical conductivity at low temperatures.

[0340] Industrial Availability

[0341] According to the solid electrolyte of the present invention and the electrolyte layer and battery using the solid electrolyte, a solid electrolyte, electrolyte layer and battery having high conductivity even in a low temperature range can be obtained. The solid electrolyte of the present invention can also be used in solid oxide fuel cells, sensors, batteries, electrodes, electrolytes, oxygen concentrators, oxygen separation membranes, oxygen permeable membranes, oxygen pumps, catalysts, photocatalysts, electrical / electronic / communication equipment, energy / environment-related equipment or optical equipment, etc.

Claims

1. A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by the following general formula (1): Ba 7-α Nb (4-x-y) Mο (1+x) M y O (20+z) ···(1) In formula (1), M is selected from Ag, Al, At, Au, Be, Bi, Br, Ca, Cd, Ce, Co, Cr, Cu, Dy, Er, Eu, Fe, Ga, Gd, Ge, Hf, Hg, Ho, I, In, Ir, La, Li, Lu, Mg, Mn, Na, Nb, Nd, Ni, Np, Os, P, Pb, Pd, Po, Pr, Pt, Pu, Re, Rh, Ru, S, Sb, Sc, Se, Si, Sm, Sn, A cation of at least one element selected from the group consisting of Sr, Ta, Tb, Tc, Te, Ti, Tl, Tm, U, V, W, Xe, Y, Yb, Zn and Zr, wherein α is a Ba deficiency and represents a value greater than 0 and less than 0.5, x represents a value greater than -1.1 and less than 1.1, y represents a value greater than 0 and less than 1.1, and z is the non-stoichiometric value of oxygen and represents a value greater than -2.0 and less than 2.0, wherein in formula (1), |x|+y≥0.01 is satisfied. 2 . The solid electrolyte according to claim 1 , wherein M is a cation of at least one element selected from the group consisting of W, V, Cr, Mn, Ge, Si and Zr. The solid electrolyte according to claim 1 , wherein x is not less than 0.06 and not more than 0.

30. The solid electrolyte according to claim 2 , wherein x is not less than 0.06 and not more than 0.

30. The solid electrolyte according to claim 3 , wherein x is 0.19 to 0.

21.

6. The solid electrolyte according to claim 2, wherein the compound has a lattice constant of The length of the a-axis, the length of the b-axis, the length of the c-axis, the angle α, the angle β, and the angle γ in degrees are respectively 5.35 <a<6.56、5.35<b<6.56、15.14<c<18.52、89<α<91、89<β<91、119<γ<121。 7. A solid electrolyte comprising a hexagonal perovskite-related compound, wherein the compound is a compound represented by any one of the following general formulae (3) to (9) and (11) to (13), <h2 style=";text-align:left;direction:ltr">Ba7Nb<h2 style=";text-align:left;direction:ltr"> (4-x) <h2 style=";text-align:left;direction:ltr"> My<h2 style=";text-align:left;direction:ltr"> (1+x) <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> (20+z) <h2 style=";text-align:left;direction:ltr"> ···(3) In formula (3), x represents a value of -1.1 to -0.01 or 0.01 to 1.1, z represents the non-stoichiometric value of oxygen and represents a value of -2.0 to 2.

0. Ba7Nb (4-y) MοM y O (20+z) ···(4) In formula (4), M is a cation of at least one element selected from the group consisting of V, Mn, Ge, Si and Zr, y represents a value of 0.01 to 1.1, z represents the non-stoichiometric value of oxygen and represents a value of -2.0 to 2.0, Ba7Nb4Mο (1-y) M y O (20+z) ···(5) In formula (5), M is a cation of at least one element selected from the group consisting of V and Mn, z is the non-stoichiometric value of oxygen and represents a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.

1. <h2 style=";text-align:left;direction:ltr">Ba7Nb<h2 style=";text-align:left;direction:ltr"> (4-y) <h2 style=";text-align:left;direction:ltr"> MOC<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> (20+z) <h2 style=";text-align:left;direction:ltr"> ···(6) In formula (6), z represents the non-stoichiometric value of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.

1. Ba7Nb (4-y) MoW y O (20+z) ···(7) In formula (7), z represents the non-stoichiometric amount of oxygen and is a value of -2.0 to 2.0, and y represents a value of 0.01 to 1.

1. Ba3W (1-x) V (1+x) O (8.5+z) ···(8) In formula (8), x represents a value of -0.8 to 0.2, z represents the non-stoichiometric value of oxygen and represents a value of -1.0 to 1.0, Ba3MO (1-x) Of (1+x) SHE (8+z) ···(9) In formula (9), x represents a value of -0.3 or more and 0.1 or less, z represents the non-stoichiometric value of oxygen and represents a value of -1.0 or more and 0.3 or less, Ba 2.6 Ca 2.4 La4Mn4O (19+z) ···(11) In formula (11), z is the non-stoichiometric value of oxygen and represents a value greater than -1.0 and less than 1.

0. <h2 style=";text-align:left;direction:ltr">La2Ca2MnO<h2 style=";text-align:left;direction:ltr"> (7+z) <h2 style=";text-align:left;direction:ltr"> ···(12) In formula (12), z is the non-stoichiometric value of oxygen and represents a value greater than -1.0 and less than 1.

0. <h2 style=";text-align:left;direction:ltr">Ba5M2Al2ZrO<h2 style=";text-align:left;direction:ltr"> (13+z) <h2 style=";text-align:left;direction:ltr"> ···(13) In formula (13), M represents any one of Gd, Dy, Ho, Er, Tm, Yb or Lu, and z represents the non-stoichiometric amount of oxygen and represents a numerical value of not less than -1.0 and not more than 1.

0. 8 . The solid electrolyte according to claim 7 , wherein the compound is a compound represented by the general formula (3), and x is 0.06 to 0.

30. 9 . The solid electrolyte according to claim 8 , wherein x is not less than 0.19 and not more than 0.

21.

10. The solid electrolyte according to claim 7, in the compound, the a-axis length, b-axis length, and c-axis length in terms of , and the α angle, β angle, and γ angle in degrees are respectively 5.35 < a < 6.56, 5.35 < b < 6.56, 15.14 < c < 18.52, 89 < α < 91, 89 < β < 91, 119 < γ < 121 for formulas (3) to (7), 5.23 < a < 6.4, 5.23 < b < 6.4, 18.96 < c < 23.19, 89 < α < 91, 89 < β < 91, 119 < γ < 121 for formula (8), 5.34 < a < 6.54, 5.34 < b < 6.54, 19.12 < c < 23.39, 89 < α < 91, 89 < β < 91, 119 < γ < 121 for formula (9), 8.85 < a < 10.83, 5.11 < b < 6.26, 14.07 < c < 17.21, 89 < α < 91, 100 < β < 104, 89 < γ < 91 for formula (11), 5.05 < a < 6.19, 5.05 < b < 6.19, 15.57 < c < 19.03, 89 < α < 91, 89 < β < 91, 119 < γ < 121 for formula (12), and 5.35 < a < 6.55, 5.35 < b < 6.55, 22.23 < c < 27.18, 89 < α < 91, 89 < β < 91, 119 < γ < 121 within the numerical range.​​ 11. The solid electrolyte according to any one of claims 1 to 10, wherein the oxide ions are O 2- The solid electrolyte used in the conductor is used at a temperature of 300 to 1200°C.

12. The solid electrolyte according to any one of claims 1 to 10, wherein when the electrical conductivity at 300° C. is measured, log[σ(Scm -1 )] has an electrical conductivity of -7 or above.

13. The solid electrolyte according to any one of claims 1 to 10, which is a solid oxide fuel cell (SOFC), a sensor, a battery, an electrode, an electrolyte, an oxygen concentrator, an oxygen separation membrane, an oxygen permeable membrane, an oxygen pump, a catalyst, a photocatalyst, an electrical / electronic / communication device, an energy / environment-related device, or an optical device.

14. The solid electrolyte according to any one of claims 1 to 10, which is used for an electrolyte layer used in a solid oxide fuel cell (SOFC), a sensor, an oxygen concentrator, an oxygen separation membrane, an oxygen permeable membrane or an oxygen pump. 15 . An electrolyte layer comprising the solid electrolyte according to claim 1 . 16 . A battery comprising the electrolyte layer comprising the solid electrolyte according to claim 15 .

17. The battery according to claim 16, which is a solid oxide fuel cell (SOFC).

Citation Information

Patent Citations

  • Massager

    JP1989048020B2

  • Novel cathode and electrolyte materials for solid oxide fuel cells and ion transport membranes

    CN101918337A